Largely Accelerated Arterial Aging in Rheumatoid Arthritis Is Associated With Inflammatory Activity and Smoking in the Early Stage of the Disease - Mong, Nikolett; Tarjanyi, Zoltan; Tothfalusi, Laszlo; Bartykowszki, Andrea; Nagy, Aniko Ilona; Szekely, Anett; Becker, David; Maurovich-Horvat, Pal; Merkely, Bela; Nagy, Gyorgy (Frontiers in Pharmacology, 2020)
Background: Rheumatoid arthritis (RA) patients have a shorter life expectancy than the general population primarily due to cardiovascular comorbidities. Objectives: To characterize arterial aging in RA. Patients and methods: Coronary calcium scores (CCS) were available from 112 RA patients; out of these patients, follow-up CCS were measured of 54 randomly selected individuals. Control CCS were obtained from the MESA database (includes 6000< participants); arterial age was calculated from CCS. Results: RA patients were significantly older (10.45±18.45 years, p<0.001) in terms of the arterial age compared to the age, gender and race matched controls. The proportion of RA patients who had zero CCS was significantly less (p<0.01) than in the MESA reference group. Each disease year contributed an extra 0.395 years (p<0.01) on the top of the normal aging process. However, the rate of the accelerated aging is not uniform, in the first years of the disease it is apparently faster. Smoking (p<0.05), previous cardiovascular events (p<0.05) and high blood pressure (p<0.05) had additional significant effect on the aging process. In the follow-up study, inflammatory disease activity (CRP>5 mg/L, p<0.05) especially in smokers and shorter than 10 years disease duration (p=0.05) had the largest impact. Conclusions: Arterial aging is faster in RA patients compared to control subjects, particularly in the first 10 years of the disease. Inflammation, previous cardiovascular events and smoking are additional contributing factors to the intensified coronary atherosclerosis progression. These data support that optimal control of inflammation is essential to attenuate the cardiovascular risk in RA.